Communist Conventions for Deductive Reasoning. (19th May 2013) - Dogramaci, Sinan
Abstract In section 1, I develop epistemic communism, my view of the function of epistemically evaluative terms such as 'rational'. The function is to support the coordination of our belief‐forming rules, which in turn supports the reliable acquisition of beliefs through testimony. This view is motivated by the existence of valid inferences that we hesitate to call rational. I defend the view against the worry that it fails to account for a function of evaluations within first‐personal deliberation. In the rest of the paper, I then argue, on the basis of epistemic communism, for a view about rationality itself. I set up the argument in section 2 by saying what a theory of rational deduction is supposed to do. I claim that such a theory would provide a necessary, sufficient, and explanatorily unifying condition for being a rational rule for inferring deductive consequences. I argue in section 3 that, given epistemic communism and the conventionality that it entails, there is no such theory. Nothing explains why certain rules for deductive reasoning are rational.